P769 Randomised feasibility study of preoperative medical nutrition therapy in adults undergoing surgery for Crohn's disease. (30th January 2023) - Wall, C; Glyn, T; Rowbotham, D; Haines, M; Bissett, I; Eglinton, T; Gearry, R
Abstract: Background: Preoperatively patients with Crohn's disease are at high risk of malnutrition. Patients requiring surgery to manage stricturing disease are often advised to follow a low residue/low fibre diet to reduce risk of bowel obstruction. This diet is usually nutritionally inadequate and may negatively affect nutritional status. Research suggests that preoperative exclusive enteral nutrition (EEN) improves nutritional status, reduces intestinal inflammation and consequently improves surgical outcomes. Recently the Crohn's disease exclusion diet has been shown to reduce intestinal inflammation in adults but its use preoperatively has not been reported. This research aimed to determine whether it is feasible to recruit and retain patients with Crohn's disease in a single-blinded, multicentre, randomised controlled trial of three preoperative nutritional therapies. Methods: Patients undergoing elective surgery to manage Crohn's disease at three New Zealand tertiary care hospitals (Christchurch, Auckland and Waikato hospitals), aged >18 years old, with body mass index (BMI) > 18.5 kg/m 2 and without recent significant weight loss were eligible to participate. Patients were randomised to six weeks of preoperative EEN, partial enteral nutrition with Phase-1 Crohn's Disease Exclusion Diet (CDED) or standard care. Nutritional and radiological assessment at baseline and preoperatively was completed and surgical outcomes recorded. Descriptive statistical analysis was undertaken. Health and Disability Ethics Committee approval was given (20/NTB/134). Results: Over 18 months (September 2020 to March 2022), 48 patients were screened and 17 were randomised. Patient characteristics were: median age 37.9 (range, 28-68) years, 9 (53%) female, 10 (59%) on biologic medication, median BMI 25.7 (range, 19.7-38.6) kg/m 2 and 2 (12%) had low fat-free mass index. Medical nutrition therapy was completed by 13/17 (76%) patients (EEN n=4, CDED n=4 and standard care n=5) and four withdrew. BMI and simplified magnetic resonance index of activity (MaRIA) score changed by a median of -0.3 (range, -1.8 to 2.1) kg/m 2 and 0.5 (range, -3 to 2) points respectively. At day 30, 10 patients had no surgical complications. Three patients had Clavien Dindo Grade 2 complications; one (standard care group) experienced fever treated with antibiotics, one (standard care group) had postoperative ileus requiring total parenteral nutrition and one (CDED group) required a blood transfusion postoperatively and antibiotics for a wound infection. Conclusion: Patients who need elective Crohn's disease surgery tolerate preoperative EEN or CDED. Use of preoperative nutrition therapies are feasible and the impact on surgical outcomes should be assessed in a larger study.